Transport of Polycyclic Aromatic Hydrocarbons in a Calcareous Wetland Soil - Soleimani, M.; Afyuni, M.; Charkhabi, A.H. (Caspian Journal of Environmental Sciences, 2013)
Knowledge of transport and degradation of polycyclic aromatic hydrocarbons (PAHs) is important in assessing PAH contamination of soils and water resources. The transport of naphthalene, anthracene, pyrene and phenanthrene was determined in a contaminated calcareous soil obtained from the Shadegan wetland (Khozestan, Iran) considering a column study in laboratory conditions. The PAHs were added to the top 5 cm of soils at 75 and 150 mg kg-1 and leachates were collected for 10 pore volumes. PAH concentrations in the leachate fractions and soils (0-5, 5-10, 10-15 and 15-20 cm depths) were determined using high pressure liquid chromatography. Results showed that naphthalene had the most mobility among the PAHs, and differences among the mobility of selected PAHs were related to their water solubility and structure. Mass balance demonstrated that among the selected PAHs, anthracene and naphthalene were the most and the least recalcitrant compounds, respectively. Hence, naphthalene could have the greatest potential to contaminate surface and ground waters which should be considered apparently.